2011
DOI: 10.1007/s10488-011-0351-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and Attitudes Towards Evidence-Based Practices in Community Child Mental Health Practitioners

Abstract: Research in the dissemination of evidence-based practices (EBPs) suggests that practitioners' knowledge of and attitudes towards EBPs influence their decisions to adopt such practices. This study investigated the relationships between practitioner background variables and EBP knowledge and attitudes, as well as the relationship between knowledge and attitudes among public sector youth direct service providers (n = 240). Findings suggest that knowledge and attitudes relate to practitioners' most advanced degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 41 publications
9
80
3
Order By: Relevance
“…Therefore, it is possible that these outliers influenced this finding. In addition, the current findings that KEBSQ scores did not significantly differ based on provider professional discipline, licensure status, or years of experience are consistent with previous research (Nakamura et al, 2011).…”
Section: Participant Knowledge Of Evidence-based Practicessupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, it is possible that these outliers influenced this finding. In addition, the current findings that KEBSQ scores did not significantly differ based on provider professional discipline, licensure status, or years of experience are consistent with previous research (Nakamura et al, 2011).…”
Section: Participant Knowledge Of Evidence-based Practicessupporting
confidence: 90%
“…In addition, providers who selected "humanistic or client-centered" as a theoretical orientation, demonstrated less knowledge of EBPs compared to providers who did not select this orientation. In contrast, previous research has found that provider age and theoretical orientation do not significantly impact knowledge of EBPs (Nakamura, Higa-McMillan, Okamura, & Shimabukuro, 2011).…”
Section: Participant Knowledge Of Evidence-based Practicescontrasting
confidence: 58%
“…Its items appear face-valid and variations of this measure have been used in numerous local investigations in the past (Nakamura et al 2011). …”
Section: Measures Background Questionnaire (Bq)mentioning
confidence: 99%
“…Practitioner buy-in is an essential element of implementation; workers have to be interested and have confidence in the evidence-based practice process (Cunningham & Duffee, 2009;Proctor, 2004), which is commonly defined as a five-step process that includes formulating a question, identifying evidence, critically assessing the evidence, applying in practice, and evaluating the application for improvements to future practice (Barth et al, 2012;Gibbs, 2003). More positive attitudes have been linked to better knowledge of RSTs among mental health practitioners (Nakamura, Higa-McMillan, Okamura, & Shimabukuro, 2011). Also, with leadership that supports its uptake, attitudes toward RSTs were found to improve for child welfare workers (Aarons & Sommerfeld, 2012).…”
Section: Attitudes Toward Rstsmentioning
confidence: 99%